Alterations in the Gut Microbiome of Individuals With Tuberculosis of Different Disease States - Wang, Yue; Deng, Yali; Liu, Nianqiang; Chen, Yanggui; Jiang, Yuandong; Teng, Zihao; Ma, Zhi; Chang, Yuxue; Xiang, Yang (Frontiers in Cellular and Infection Microbiology, 2022)
Objective There is evidence that the gut microbiota play a regulatory role in the occurrence and progression of tuberculosis. The purpose of the current study was to explore the alterations in gut microbiome under different tuberculosis disease stages in the Uyghur population, clarify the composition of microbial taxonomy, search for microbial biomarkers and provide innovative ideas for individual immune prevention and for control strategies. Design A case–control study of Uyghur individuals was performed using 56 cases of pulmonary tuberculosis (PTB), 36 cases of latent tuberculosis infection (LTBI) and 50 healthy controls (HC), from which stool samples were collected for 16S rRNA gene sequencing. Results The results showed that the alpha diversity indexes of the PTB group were lower than those of the other two groups (P <0.001), while only observed species were different between LTBI and HC (P <0.05). Beta diversity showed differences among the three groups (P = 0.001). At the genus level, the relative abundance of Bifidobacterium and Bacteroides increased, while Roseburia and Faecalibacterium decreased in the PTB group, when compared with the other two groups, but the changes between the LTBI and HC groups were not significant. The classifier in the test set showed that the ability of the combined genus to distinguish between each two groups was 81.73, 87.26, and 86.88%, respectively, and the validation efficiency was higher than that of a single screened genus. Conclusion The gut microbiota of PTB patients was significantly disordered compared with LTBI and HC, while the changes of LTBI and HC were not significant. In the future, gut microbiota could be used as a non-invasive biomarker to assess disease activity.